Analisis Pengaruh Transformasi Struktural Pada Bidang Teknologi Terhadap Kemajuan Industri Di Kota Surabaya - Clemment Marvello Fedihartono; Nerissa Arcellya Virjannah; Muhammad Yasin (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
Globalization becomes inevitable for almost all aspects of life, especially in the industrial sector. Globalization has brought the industry to experience a structural transformation that focuses on technology. The structural transformation experienced by the industrial sector may have positive and negative effects, not only for the industry itself, but for the surrounding communities and the environment. The research method used in this research is initiative descriptive qualitatively by writing observation written, with data in the form of field notes. Technological advances are tested on the areas of the industry, is; Production, Research and Development / Research and Development (R & D), operational management, logistics and supply chain management, finance and accounting, human resources (HR), marketing and sales, information technology (IT), laws and compliance, and customer service